Mathematical model of separation of magnetic ore - Lyashko, S.I.; Zub, S.I.; Zub, S.S. (Reports of the National Academy of Sciences of Ukraine, 2018)
The magnetic interaction of an ore with a field in the flight is investigated. New mathematical models of a magnetic ore and the motion of a paramagnetic body in the uniform field of gravity under the influence of a magnetic force are created. Our estimates and the mathematical modelling indicate the magnetic ore separation. A scheme of the magnetic field distribution is presented. Optimization parameters are defined.